METODE PEMBELAJARAN PADA MATA PELAJARAN AL QUR’AN HADITS DI TINGKAT MADRASAH ALIYAH - Siti Maratus Solekah; Iriansyah Iriansyah; Rofiqoh Rofiqoh; Muhammad Rizal Ansori; Jajang Rustandi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
The aim of this study is to examine the application of teaching methods in the Al-Qur'an and Hadith subjects at the Madrasah Aliyah level. The learning process is an activity that transforms knowledge, attitudes, and skills. Teachers are expected to develop students' learning capacities, basic competencies, and potential to the fullest. The learning process should be student-centered, encouraging active participation from students. This approach enables students to develop independent learning strategies and take part in the planning, implementation, and assessment of the learning process itself. Therefore, the experiences of the students are prioritized in determining the starting point for the learning activities.